2001
DOI: 10.1021/la0102612
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Thin Films Formed by Salt-Induced Structural Changes in Multilayers of Poly(acrylic acid) and Poly(allylamine)

Abstract: We report here on the influence of changes in the solution salt concentration on the structure of multilayers of weak polyelectrolytes. For poly(acrylic acid) (PAA) and poly(allylamine) (PAH) multilayers assembled by the layer-by-layer process in the presence of sodium chloride, washing with pure water after deposition of each layer produces films with considerable surface roughness (root-mean-squared (rms) roughness ∼17 nm for a 10 layer film), as assessed by scanning force microscopy. In contrast, relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
249
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(251 citation statements)
references
References 17 publications
0
249
0
2
Order By: Relevance
“…Moreover, the pore size can be controlled to 17 nm based on sodium chloride addition while preparing the membrane. 8 A modification of the nanoporous characteristics of the membranes can be achieved by changing the components of the membranes. We found that molecular-size nanopores can be achieved in a PIC membrane composed of PSS and PLL, where the penetration of the molecular species is strongly influenced by the molecular size; i.e., species with molecular weights less than that of 110 g/mol can penetrate through the PIC membrane, whereas larger species are excluded by the membrane (Fig.…”
Section: ·2·1 Separating Membranementioning
confidence: 99%
“…Moreover, the pore size can be controlled to 17 nm based on sodium chloride addition while preparing the membrane. 8 A modification of the nanoporous characteristics of the membranes can be achieved by changing the components of the membranes. We found that molecular-size nanopores can be achieved in a PIC membrane composed of PSS and PLL, where the penetration of the molecular species is strongly influenced by the molecular size; i.e., species with molecular weights less than that of 110 g/mol can penetrate through the PIC membrane, whereas larger species are excluded by the membrane (Fig.…”
Section: ·2·1 Separating Membranementioning
confidence: 99%
“…[31] Others have observed that polyelectrolyte nanocomposite thin films are highly compact, have a nanoporous structure and can limit the diffusion of small molecules such as ferricyanide. [15,16,22] Given that the nanocomposite films described here do undergo significant structural changes upon oxidation and reduction, these films are likely very compact and may posses nanoporosity as seen in other polyelectrolyte thin films. Actual electrode response Anticipated electrode response in the absence of mass transfer limitations in the nanocomposite film Figure 5.…”
Section: Electron Transfer and Mass Transfer At The Sensor Surfacementioning
confidence: 99%
“…For all the enzymes, one would expected that the enzyme is highly intercalated with the redox polymer layer, given the highly charged nature of each macromolecule in the multilayer structure. [7,13,15,16,21,22] The SPR signal can be directly related to the surface concentration of proteins with a shift of θ SPR by 1° degree corresponding to the deposition of 10 ng/mm 2 of protein. [23] Because the SPR signal can be alternatively recorded in RI units or angle θ SPR , the surface concentration of enzyme for each deposition step was easily found using the conversion factor of 7x10 Assuming the density of protein to be 1.3 g/cm 3 and a densely packed layer, [12] the thickness of the first deposited enzyme layer was approximately 19 Å.…”
Section: Thin Film Assembly and Structurementioning
confidence: 99%
See 2 more Smart Citations